PENGARUH MEKANISME ISLAMIC CORPORATE GOVERNANCE TERHADAP KINERJA BANK SYARIAH DI INDONESIA BERDASARKAN MAQASHID SYARIAH INDEKS - Anton, Anton (BISNIS, 2018)
To be able to realize the business goals and social objectives of Islamic banks need to be supported by Islamic corporate governance mechanisms that protect the rights and interests of all stakeholders who are subject to the rules of sharia. The purpose of this study was to determine the effect of Islamic corporate governance mechanism variables on the performance of Islamic banks in Indonesia based on the maqashid sharia index. The results showed that the number and education of the Sharia Supervisory Board had a significant effect. While concurrent positions and meetings of the Sharia Supervisory Board have no significant effect on the performance of Islamic banks in Indonesia based on the maqashid sharia index.